Kesejahteraan Keuangan Keluarga Usia Pensiun: Literasi Keuangan, Perencanaan Keuangan Hari Tua, dan Kepemilikan Aset - Aulia, Nadia; Yuliati, Lilik Noor; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2019)
This study aims to analyze the effect of financial literacy, retirement planning, and asset ownership on family’s financial wellbeing at retirment age. Sample in this research was 120 families with a husband or wife in retiress age (55-65 years old) as a respondent. Respondents were chosen purposively, 60 respondents in each urban and rural area. The research did in Bandar Lampung city as an urban area and Pringsewu district as a rural area. Data were analyzed using descriptive analysis, a independent sample t-test, and multiple linear regression. The result showed that level of education, job status, and average of income were different significant between urban and rural area, and average of the family in urban area was higher than rural area. Index average of financial literacy and financial well-being in rural area was lower than urban area. Percentage of retirement planning ownership of  respondent’s in urban area was higher than respondents in rural area. Average of asset ownership (material asset and financial asset) also higher in urban than rural area. The factors that have positive significant effect on family’s financial wellbeing at retirees age were region, education, financial literacy, and retirement planning.